Modelling and optimisation of sound absorption in replicated microcellular metals - Otaru, A.J.; Morvan, H.P.; Kennedy, A.R. (Elsevier, 2018)
Wilson's poroacoustic model has been shown to be an accurate predictor of sound absorption in porous metals with bottleneck type structures. When used to optimise pore structures, using porosity and permeability as variables, the most broadband absorption is predicted for the highest porosity achievable (approximately 70%) and for a permeability of the order 10−10 m2. Although performance close to that for glass wool is not possible, with these porosities, specific strength and stiffness exceeding those for many polymers are obtained, making these materials viable for load bearing components with credible soundproofing.